2022
DOI: 10.1007/s10047-022-01329-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of citrate in cardiovascular system and clot circuit in critically ill patients requiring continuous renal replacement therapy

Abstract: We aimed to evaluate the impact of citrate on hemodynamic responses and secondary outcomes, including the filter life span, metabolic complications, and levels of inflammatory cytokines, in critically ill patients who required CRRT compared with those who underwent the heparin-free method. This prospective, multicenter, open-label randomized trial compared regional citrate anticoagulation (RCA) with a heparin-free protocol in severe acute kidney injury (AKI) patients who received continuous venovenous hemodiaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In the RCA group, the post-filter ionized calcium concentration in most studies was kept at 0.25–0.35 mmol/L [ 32 , 37 , 43 45 ]. And the targeted systemic ionized calcium levels in most studies were kept at 0.9–1.2 mmol/L or 1.0–1.35 mmol/L [ 41 , 44 47 ]. Thus, we consider the assumption of transitivity to be valid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the RCA group, the post-filter ionized calcium concentration in most studies was kept at 0.25–0.35 mmol/L [ 32 , 37 , 43 45 ]. And the targeted systemic ionized calcium levels in most studies were kept at 0.9–1.2 mmol/L or 1.0–1.35 mmol/L [ 41 , 44 47 ]. Thus, we consider the assumption of transitivity to be valid.…”
Section: Resultsmentioning
confidence: 99%
“…Only a small subset of trials provided information on the length of hospital stay, with 4 RCTs [ 43 , 44 , 48 , 49 ] involving 3 anticoagulation options. Therefore, NMA for this outcome was not performed.…”
Section: Resultsmentioning
confidence: 99%
“…However, anticoagulant use is limited by the risk of bleeding. Another technique to limit thrombosis in the extracorporeal circuit is regional citrate anticoagulation or CD, which has shown promising results in previous studies [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clotting scores signi cantly increased in the post-dilution mode compared with the pre-dilution mode, with a maximum value of less than 3. We previously reported that citrate does eliminate the need for heparin during HD [25] but did not prolong the circuit life span in continuous venovenous hemodia ltration in the post-dilution mode [24]. Previous studies have suggested that some clotting did occur during HD or continuous renal replacement therapy and that citrate can attenuate the need for heparin [28,29] but not abolish it entirely.…”
Section: Effect On Anemiamentioning
confidence: 99%
“…However, the use of these anticoagulants is limited by the risk of bleeding. Another technique to limit thrombosis in the extracorporeal circuit is regional citrate anticoagulation or CD, which showed promising results in previous studies [24,25].…”
Section: Effect On Anemiamentioning
confidence: 99%